ORGANIZATION OF COGNITIVE ACTIVITY OF STUDENTS IN THEORIES AND PRACTICES OF LABOR EDUCATION - O.Ye. Sushentsev (Academy of Cognitive and Natural Sciences, 2008)
In the article an author specifies the concepts of activity, cognitive activity, describe the essence of the problem of organization the cognitive activity on the labour teaching lessens.